2018
DOI: 10.1542/peds.2017-3510
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation Interventions and Parenting in Low- and Middle-Income Countries: A Meta-analysis

Abstract: Early childhood stimulation interventions improve several distinct aspects of maternal parenting. Improvements in parenting capacities may serve as key mechanisms by which these programs benefit ECD outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 38 publications
4
90
2
6
Order By: Relevance
“…Stimulation interventions have been implemented effectively at scale with mothers in diverse cultural settings (e.g., Colombia, Jamaica, Pakistan), demonstrating positive impacts on maternal practices and ECD. [55] An emerging body of research in LMICs has also demonstrated the effectiveness of father involvement interventions for promoting paternal stimulation and early child development outcomes. For example, a parenting intervention in Vietnam encouraged fathers to responsively interact with their infants and work together with the mother as part of a parenting team.…”
Section: Plos Onementioning
confidence: 99%
“…Stimulation interventions have been implemented effectively at scale with mothers in diverse cultural settings (e.g., Colombia, Jamaica, Pakistan), demonstrating positive impacts on maternal practices and ECD. [55] An emerging body of research in LMICs has also demonstrated the effectiveness of father involvement interventions for promoting paternal stimulation and early child development outcomes. For example, a parenting intervention in Vietnam encouraged fathers to responsively interact with their infants and work together with the mother as part of a parenting team.…”
Section: Plos Onementioning
confidence: 99%
“…Little is known about the long-term impact of ESB during pregnancy on child development. However, we know that stimulation-focused interventions for caregivers are effective in creating more nurturing home environments, improving mother-child interactions, and increasing maternal knowledge (38). Responsive caregiving is a continuum and further research is needed to better understand its role throughout different stages of early childhood development.…”
Section: Resultsmentioning
confidence: 99%
“…A generalized estimating equations (GEE) modi ed Poisson model was used for bivariate and multivariable analyses, taking into account clustering by using an exchangeable working correlation (32). The Kauermann-Carroll bias correction was used to account for potential small-sample bias in the standard errors, since the trial had fewer than 40 clusters (33,34). For the bivariate model, the correlation between the early stimulation factor score and each covariate was evaluated.…”
Section: Data Management and Analysismentioning
confidence: 99%